Pengaruh Perencanaan Pembelajaran dan Kreativitas Guru terhadap Hasil Belajar Mata Pelajaran SKI Siswa Kelas VIII MTs.Yasiba Kota Bogor - Ekawati; Srihartini, Yusi; Kartika, Ika; Abdulloh, Parid (Jurnal Dirosah Islamiyah, 2024)
This research aims to test and find out empirical data regarding the influence of learning planning and teacher creativity on the learning outcomes of Islamic culture history subjects. In this study, the authors used a quantitative approach. The sample of this study was 81 respondents from class VIII MTs Yasiba students. The population in this study was all MTs students. Yasiba, which has 812 students in the even semester of the 2023-2024 academic year. Data collection is carried out using observation techniques, documentation and questionnaires. The data analysis technique in this research uses simple regression and multiple regression data analysis techniques with the help of SPSS version 17 software.Based on field data and analysis, this study found : (1) There was an influence of learning planning on SKI learning outcomes, obtaining an R square score of 0.331 or 33.1%. This means that the learning planning variable influences SKI learning outcomes by 33.1% and the remaining 66.9% is determined by other factors outside the regression model. (2) There is an influence of teacher creativity on SKI learning outcomes. In this determination test, an R square value of 0.379 or 37.9% was obtained%. This means that the variable teacher creativity in students' SKI learning outcomes is 37.9% and the remaining 62.1% is determined by other factors outside the regression model. (3) There are results from the determination test, a correlation value (R) of 0.673 is obtained. This shows that there is a correlation between learning planning and teacher creativity together in SKI learning outcomes of 0.673.